Postoperative inflammation as a possible cause of portal vein thrombosis after irreversible electroporation for locally advanced pancreatic cancer - Su, Jun-Jun (World J Gastroenterol, 2017)
Portal vein thrombosis (PVT) is a rare but serious postoperative complication associated with irreversible electroporation (IRE). We report a case of postoperative PVT in a 54-year-old woman who underwent IRE for locally advanced pancreatic cancer. Drain removal and discharge of the patient from the hospital were scheduled on postoperative day (POD) 7; however, a magnetic resonance imaging scan revealed the presence of PVT. We suspected postoperative inflammation in the pancreas as the main cause of PVT. However, the patient did not undergo any medical treatment because she did not have any clinical symptoms, and she was discharged on POD 8.